2018
DOI: 10.1111/jbi.13448
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Gondwanan breakup on the biogeographic history of the ziziphoids (Rhamnaceae)

Abstract: Aim:We investigated whether the fossil-rich and cosmopolitan buckthorn family (Rhamnaceae, dating back to the Cretaceous) was influenced by vicariance events following the Gondwanan breakup. To answer this question, we focused on the ziziphoid lineage of the buckthorn family, because extant ziziphoid taxa comprise tribes and genera exclusively or at least predominantly distributed in the Southern Hemisphere (Australia, Africa, and South America).Location: World-wide. Methods:We generated a DNA alignment of 26,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…A well‐resolved phylogeny, representative taxon sampling, and reliably identified and dated fossils have been shown to be extremely important for the estimation of realistic divergence times (e.g., Linder et al, ; Mao & Liu, ; Mao et al, ; Muellner et al, , Hauenschild et al, ). Although the relatively good fossil record for Betulaceae has encouraged studies using molecular clock dating, inferring realistic divergence times is still challenging, mainly due to the relatively poor taxon sampling and low phylogenetic resolution (Forest et al, ; Xing et al, ; Larson‐Johnson, ).…”
Section: Discussionmentioning
confidence: 99%
“…A well‐resolved phylogeny, representative taxon sampling, and reliably identified and dated fossils have been shown to be extremely important for the estimation of realistic divergence times (e.g., Linder et al, ; Mao & Liu, ; Mao et al, ; Muellner et al, , Hauenschild et al, ). Although the relatively good fossil record for Betulaceae has encouraged studies using molecular clock dating, inferring realistic divergence times is still challenging, mainly due to the relatively poor taxon sampling and low phylogenetic resolution (Forest et al, ; Xing et al, ; Larson‐Johnson, ).…”
Section: Discussionmentioning
confidence: 99%
“…With priors that are too narrow, the analysis will often produce clade ages that are much too young, and this is especially likely in a group with such a sparse fossil record as Meliaceae. Priors are crucial. As Hauenschild et al (2018) observed, vicariance is often ruled out for clades in which reconstructed age estimates are younger than continental breakup. However, they noted that the young ages estimated "may also be due to overly small highest posterior density intervals of the time estimated based on too narrowly set priors, and vicariance thereby may be erroneously ruled out (Beaulieu et al, 2013).…”
Section: Chronological Analysismentioning
confidence: 99%
“…2-4 and Supplementary Figs. [21][22][23][24][25][26][27][28][29][30][31] and Supplementary Videos 2-3). Eophylica can be distinguished from Phylica on the basis of the number of sepals and the absence of petals.…”
Section: Resultsmentioning
confidence: 99%